A person-centered expectancy motivation model - Hiatt, Aaron (Center for Leadership Equity and Research)
Intrinsic, extrinsic, and Maslowian motivation (specifically, self-actualization) are synthesized to repurpose traditional expectancy theory (in which motivational force is a product of valence, instrumentality, and expectancy) to accommodate the subjective human experience. Intrinsic and extrinsic motivation are rationalized as a single theoretical construct in the context of self-actualization. Self-actualization is used to reformulate expectancy theory to describe motivational force as a product of the squares of the valence that a person associates with an outcome, and his/her perceived ability to achieve the outcome. Discussion centers on the relative power of motivational force, motivation as a uniquely person-centered phenomenon, and implications in path-goal leadership theory.